Effects of 6 weeks in-season flywheel squat resistance training on strength, vertical jump, change of direction and sprint performance in professional female soccer players - Javier Pecci; Alejandro Muñoz-López; Paul Jones; Borja Sañudo (Termedia Publishing House, 2022)
Flywheel resistance training devices (FRTD) is shown effective in improving strength, sprinting, jumping and changes of direction (COD) performance in male soccer players, however, this is not elucidated in female soccer players. We aimed to assess the effect of FRTD on these physical abilities in females soccer players. 24 professional female soccer players (age: 20.4±2.6 years) were randomly assigned to a flywheel training group (FWTG) that trained twice a week for 6 weeks on a rotary inertia device with an initial volume of 3 sets of 6 repetitions and an inertia of 0,025 kg·m-2, increasing intensity and volume or a control group (CG) that did not performed any additional resistance training program. Concentric peak torque of the knee extensors (CONEXT) and flexors (CONFLEX), eccentric peak torque of the knee extensors (ECCEXT) and flexors (ECCFLEX) at 60°·s -1 on an isokinetic dynamometer, countermovement jump (CMJ) height, COD and 30-metres sprint were assessed. Significant time by group interactions were found in CONEXT (p = 0.002; η²p = 0.425), CONFLEX (p = 0.037; η²p = 0.22), ECCEXT (p = 0.002; η²p = 0.43) and ECCFLEX (p = 0.008; η²p = 0.334). No time by group effect wasfound in CMJ (p = 0.061; η²p = 0.182), COD (p = 0.067; η²p = 0.184) orsprint (p = 0.926; η²p = 4.979·e-4). In conclusion, 6 weeks of flywheel squat training improved strength (especially eccentric strength) but not soccer-specific abilities such as jumping, changing of direction or sprinting in professional soccer players.